Single cell stable isotope probing in microbiology using Raman microspectroscopy. - Wang, Y; Huang, W; Cui, L; Wagner, M (Elsevier, 2016)
Microbial communities are essential for most ecosystem processes and interact in highly complex ways with virtually all eukaryotes. Thus, a detailed understanding of the function of such communities is a fundamental prerequisite for microbial ecologists, applied microbiologists and microbiome researchers. Using single cell Raman microspectroscopy, biochemical fingerprints of individual microbial cells can be obtained in an externally label-free and non-destructive manner. If combined with stable isotope probing (SIP), Raman spectroscopy can directly reveal functions of single microorganisms in their natural habitat. This review provides an update on various SIP-approaches suitable for combination with different Raman scattering techniques and illustrates how single cell Raman SIP can be directly combined with the omics-centric analysis pipelines to investigate microbial communities.